Pengaruh Komite Audit, Reputasi Auditor, Likuiditas, Dan Rasio Hutang Terhadap Kebijakan Dividen Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Real Estate Dan Building Construction Yang Terdaftar Di Bursa Efek Indonesia - Annisa Nauli Sinaga; Catherine Pangestu; Christina Christina (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The purpose of this study is to see the effect of the Audit Committee, Auditor's Reputation, Liquidity, and Debt Ratio on Dividend Policy with Profitability as a Moderation Variable in Real Estate and Building Construction Companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This research is a quantitative research. The data used is secondary data obtained from the official website of the Indonesia Stock Exchange www.idx.co.id. The population in this study were all Real Estate and Building Construction companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period as many as 75 companies, with a purposive sampling technique so that the sample that met the criteria was 17 companies. From this research it can be seen that the Audit Committee, Auditor's Reputation, Liquidity and Debt Ratio simultaneously have a significant and significant effect on dividend policy and Auditor's reputation has a partial and significant negative effect on dividend policy, and the Audit Committee, liquidity and debt ratio partially have no effect and not significant to dividend policy. Keywords: Audit Committee, Auditor's Reputation, Debt to Equity Ratio, Dividend Policy, Profitability